Stigma perception and determinants among patients with type 2 diabetes mellitus in Iraq - Taqi M. J. Taher; Hussein A. Ahmed; Ali A. Abutiheen; Shaymaa A. Alfadhul; Hasanain F. Ghazi (SpringerOpen, 2023)
Abstract Background and purpose Diabetes mellitus (DM) is a leading cause of death worldwide. Stigma is a sign of social disgrace occurring within public relations, and it is linked with many health conditions including diabetes. Stigma could worsen the disease course, reduce treatment adherence, and affect the quality of life of diabetic patients. The objective of this study was to assess the magnitude of diabetic stigma among patients with type 2 DM. Methods In this analytic cross-sectional study, data collection was performed from June 1, 2022, until November 1, 2022, et al.-Najaf City, Iraq. A consecutive sample of 429 patients with type 2 DM was interviewed using the Arabic version of the type 2 Diabetes Stigma Assessment Scale (DSAS-2), which is a validated tool. The total diabetic stigma score, treated differently score, self-stigma score, and blame and judgment score were estimated. Results The mean age of the sample was 56.6 years, and males represented 61.8% of them. The total diabetic stigma score mean was 51.72. The question regarding people's judgment of food choices showed the highest rate (53%) among patients. Problematic stigma appeared in 24.71% of DM patients. Lower educational level, being divorced or widow, age above 50 years, being unemployed or housewife, and lower income showed significantly higher diabetic stigma scores. Conclusion One-quarter of type 2 DM patients showed problematic stigma. The mean diabetic stigma score was significantly higher among patients with lower education, divorced or widow status, older age, unemployment or housewife category, and low-income status.